Gargalos à Expansão da Produção e Comercialização do Algodão Agroecológico. O Caso de uma Associação de Produtores Familiares no Nordeste do Brasil - Luis Carlos Zucatto (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
BOTTLENECKS TO THE EXPANSION OF PRODUCTIONAND COMMERCIALIZATION OF AGRO-ECOLOGICAL COTTON:THE FAMILY FARMERS ASSOCIATION IN NORTHEAST BRAZIL CASEAbstractThis study aims to identify bottlenecks to the expansion of production and commercialization ofagro-ecological cotton produced by Family farmers in the Northeast of Brazil associated to the ADEC(Association for Educational and Cultural Development, Taua – Ceará). In conducting the study weobserved a qualitative approach in collecting data through interviews and the Web Pages of organiza-tions involved in this activity. As main results, the study suggests that buyers of Adec agroecologicalcotton are companies that make up the Justa Trama Network and Veja (French company that usesthe product for the production of shoes and clothing with fair trade appeals). There are evidencesthat the scale would constitute a relevant bottleneck for the expansion of production and marketingof this product. The production regularity, in the Adec, is strongly influenced by farmers turnover inagroecological cotton production, as well as climate issues. Already, the lack of formation for floatingcapital would be a major bottleneck for production financing. The price at the time of the data collection,was R$ 25.00 per arroba and watches since 2006. The main contribution of the study highlights theStrategy for Agroecology and Market Group, which is articulated as an innovative element in relationto the form of organization of agroecological cotton production and pricing for the same.